PHOTOMETRY OF THE ASYNCHRONOUS POLAR V1500 CYG AT VARIOUS PHASES OF THE SYNODICAL CYCLE IN 2005-2006 YRS - Litvinchova, A. A.; Pavlenko, E. P.; Shugarov, S. Yu. (Одеські астрономічні публікації, 2007)
We present photometry of the asynchronous polar Nova Cygni 1975 = V1500 Cyg in 2005-2006. The brightness of star in R in the 2006 was increased on 0:53m in comparison with 2005. We constructed and analyzed the light curves of V1500 Cyg in the all intervals of phases of the cynodical cycle. Based on the photometric observations durin orbital O-C shown of dependence from phases of beat period in minima and maxima, that point to existence of additional asymmetric irradiation. At the beat phase 0.73 we found that the profile of the "orbital" light curve of V1500 Cyg differs from the ordinary profile of orbital light curve caused by the reflection effect.